The lived experiences of intensive care nursing students exposed to a new model of high-fidelity simulation training: a phenomenological study - Angelo Dante; Vittorio Masotta; Alessia Marcotullio; Luca Bertocchi; Valeria Caponnetto; Carmen La Cerra; Cristina Petrucci; Celeste Marie Alfes; Loreto Lancia (BMC, 2021)
Abstract Background In postgraduate intensive care nursing courses, high-fidelity simulation is useful to prepare students to guarantee safe and quality care of critically ill patients. Surprisingly, this issue has not attracted sufficient attention in the literature, and it is not clear whether the linear application of the traditional high-fidelity simulation method based on prebriefing, the simulation session and debriefing, can serve as empirical reference in postgraduate students' education. The aim of this study was to investigate the lived experiences of postgraduate students receiving multiple exposures to an innovative high-fidelity simulation design based on Kolb's Experiential Learning Theory. Methods A phenomenological study was conducted at an Italian University involving a purposive sample of 15 nursing students attending the postgraduate intensive care course. Audio-recorded face-to-face in-depth interviews were held by a researcher in a dedicated room complemented with non-verbal communication outlined in the field notes. Thematic analysis was used to analyse the transcribed data. Results Three themes and ten categories were derived from the data analysis. The themes included pragmatic learning experience, the emotional path, and confidence. Conclusions Multiple exposure to high-fidelity simulation was lived as a pragmatic learning experience enhancing the students' ability to apply theory into practice. This novel approach also contributed to the transition from negative to positive feelings and improved students' confidence about technical and non-technical skills when caring for a critically ill patient.